2022
DOI: 10.3389/fsurg.2022.809098
|View full text |Cite
|
Sign up to set email alerts
|

Precise Localization in Craniotomy With a Retrosigmoid Keyhole Approach: Microsurgical Anatomy and Clinical Study

Abstract: ObjectiveWe aimed to explore a method of precise localization within craniotomy based on skull anatomical landmarks via the suboccipital retrosigmoid approach.MethodCraniometric measurements were taken from 15 adult dry skulls and eight cadaver head specimens. In the anatomical study, the keypoint corresponded to the transverse-sigmoid sinus junction's corresponding point on the external surface of the temporal mastoid process, eight cadaveric heads underwent a simulated craniotomy using the suboccipital retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In our study, we observed that the distance from the TMN to the IM point was found to be 19.2 mm (16.1; 23.2) cranially. Jian et al suggested that the exact location of the burr hole should be 12 mm directly above the highest point of the mastoid groove [ 5 ]. So, considering that the burr hole cover has a diameter of 14 mm, the upper boundary of the burr hole would be approximately 0.2 cm away from the IM point of the TSSJ according to our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed that the distance from the TMN to the IM point was found to be 19.2 mm (16.1; 23.2) cranially. Jian et al suggested that the exact location of the burr hole should be 12 mm directly above the highest point of the mastoid groove [ 5 ]. So, considering that the burr hole cover has a diameter of 14 mm, the upper boundary of the burr hole would be approximately 0.2 cm away from the IM point of the TSSJ according to our study.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several efforts to pinpoint the anatomical markers that represent the TSSJ. Superficial reference points of the cranium, including the asterion, the superior nuchal line, the line connecting the inion, and the root of the zygomatic arch are employed to identify significant intracranial structures [ 5 ]. To summarize, the approaches have the following drawbacks: firstly, there are instances where the skull sutures cannot be clearly distinguished, resulting in ineffective localization of the TSSJ.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 14 Furthermore, although plain CT is widely utilized as a preoperative imaging modality for MVD to obtain anatomical information about the mastoid air cells, CTA can also provide essential information on the transverse sinus and sigmoid sinus location, which is important for lateral suboccipital craniotomy. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…The localization of the posterior aspect of the SS and the transverse-sigmoid junction is extensively studied compared to the paucity of signs focusing on the presigmoid territory. [ 3 , 5 ] In addition, the constant refinement of the presigmoid approaches to achieve minimal invasiveness renders the new modified minimally invasive approaches to have shorter incisions and focused skin incisions. This will shrink the exposed bony surface and lessen the accessible surface or skeletal anatomical indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variability of this landmark in terms of age, gender, or racial characteristics can be validated in the future studies. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%